1986
DOI: 10.1159/000177172
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Protein Fractions of Human Milk during Lactation

Abstract: The changes in the absolute and relative contents of α- and ĸ-caseins, lactoferrin, α-lactalbumin, serum albumin and lysozyme in human milk have been studied through the period of lactation. Protein fractions of 209 samples were analyzed by a discontinuous poly-acrylamide gel electrophoresis method, β- and ĸ -caseins decreased from colostrum to mature milk although their relative percentages remained constant. They accounted for 12–15 and 9–13% of the total protein in human milk, respectively. Lactoferrin decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
13
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 15 publications
6
13
0
Order By: Relevance
“…Recovery studies showed close agreement between the theoretical and measured protein concentrations in dilution-overloadind assays (linear recovery on large ranges of concentrations with mean percentage very close to 100%). Results of the measurements of nine proteins performed together in a great number of human mature milk samples are, for the most part, in good agreement with those previously reported in past years (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), using different techniques and, the most often, restricted to the determination of the one or another of these proteins. Emergence of new analytical procedures in the late years, such as conventional or microparticleenhanced immunonephelometry, today allows major proteins of human milk to be analyzed with sensitivity, easiness, and singleness of methodologies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recovery studies showed close agreement between the theoretical and measured protein concentrations in dilution-overloadind assays (linear recovery on large ranges of concentrations with mean percentage very close to 100%). Results of the measurements of nine proteins performed together in a great number of human mature milk samples are, for the most part, in good agreement with those previously reported in past years (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), using different techniques and, the most often, restricted to the determination of the one or another of these proteins. Emergence of new analytical procedures in the late years, such as conventional or microparticleenhanced immunonephelometry, today allows major proteins of human milk to be analyzed with sensitivity, easiness, and singleness of methodologies.…”
Section: Discussionsupporting
confidence: 89%
“…Among these components, milk-specific and plasma proteins, such as beta-casein (␤-CN), kappacasein (-CN), alpha-lactalbumin (␣-LA), serum albumin (SA), lactoferrin (LF), lysozyme (LZ), immunoglobulins A (IgA), C3, and C4 complement fractions have important nutritious and immunological functions. Numerous methods, such as fast protein liquid chromatography (2,3), polyacrylamide gel electrophoresis (4,5), ion-exchange chromatography (6), enzyme activity measurement (7), and various types of immunoassays (8 -14), have been reported to assay these proteins in human milk. Most of these techniques lack sensitivity and moreover require sample pretreatment or long incubation periods.…”
mentioning
confidence: 99%
“…The J16 clone is homologous to the 3' terminus of the lactoferrin sequence, which encodes a single glycosylated polypeptide of -70-80,000 Mr (Teng et al, 1986) which like transferrin has iron binding properties, and has been found in human (Sanchez-Pozo et al, 1986;Hegnhj et al, 1986) exocrine secretions, and has been isolated from milk and neutrophilic leucocytes (Moguilevsky et al, 1985). A mouse cDNA clone was isolated form a uterine lambda gtl 1 library by immunoscreening and was found to have -70% homology with the human sequence (Metz-Boutigue et al, 1984) recently cloned from a myeloid library using an oligonucleotide (Rado et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…A parallel study was simultaneously car ried out to examine the changes in the pro tein fractions o f human milk during lactation [19].…”
Section: ]mentioning
confidence: 99%